2010
DOI: 10.1177/0022034509357881
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss, Apolipoprotein E, and Decline in Delayed Word Recall

Abstract: Our previous research suggests an association between a low number of teeth and increased risk of dementia. The aim of the present study was to determine if a low number of teeth is specifically related to memory decline as evidenced by low Delayed Word Recall scores. In addition, we examined the combined effect of a low number of teeth and the apolipoprotein E ϵ4 allele on Delayed Word Recall scores. We hypothesized that the scores of those who had the allele and a low number of teeth (0-9) would decline more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 30 publications
2
80
2
3
Order By: Relevance
“…Our findings are not consistent, however, with previous studies that found edentulism to predict more rapid cognitive decline and greater incidence of dementia (6,24). In fact, our study found a slower cognitive decline in edentulous participants.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings are not consistent, however, with previous studies that found edentulism to predict more rapid cognitive decline and greater incidence of dementia (6,24). In fact, our study found a slower cognitive decline in edentulous participants.…”
Section: Discussioncontrasting
confidence: 99%
“…Whereas many studies report associations of fewer teeth and complete tooth loss with poorer cognitive function (3,5,14,2224), evidence regarding the association between actual periodontal disease and cognitive ability is mixed (3,68,14,15). Furthermore, periodontal disease exposure in earlier studies has been assessed with measures, such as the community periodontal index (CPI), which are based on clinical signs that do not provide much information about the underlying biology of periodontal disease (7).…”
Section: Introductionmentioning
confidence: 99%
“…Salient points are that periodontal disease is co-morbid with clinically demented subjects [4][5][6][7]. Tooth loss in early and midlife has consequences for poor memory in later life [4,[7][8][9][10][11][12]. A prospective longitudinal study reported by Ide et al [7] upholds the view that periodontitis is associated with a marked increase in cognitive decline, which is independent of base line cognition, in men with a mild to moderate clinical diagnosis of dementia.…”
Section: Making a Case For Periodontitis As A Risk Factor For Alzheimmentioning
confidence: 99%
“…First, there are significant correlations between the rate of cognitive decline and measures of periodontal disease progression, such as pocket depth, alveolar bone loss and tooth loss [37]. Currently, the relevance of newly identified risk factor, cognitive deficit for periodontitis [8], is more difficult to measure and pinpoint. We have suggested an explanation following our studies performed in the P. ginigivalis mono-infection model of periodontal disease in apolipoprotein E knockout (ApoE -/-) mice (see section on blood-brain barrier below).…”
Section: Periodontal Diseasementioning
confidence: 99%
“…In 144 nuns, those encoding APOEɛ4 and who had fewer teeth experienced more rapid cognitive decline than those with neither or either of these risk factors (188). Clinical and epidemiological studies showed that loss of teeth is associated with poor memory (6,96,187,189).…”
Section: Genetic Nutritional and Environmental Factors Promoting Admentioning
confidence: 99%